Role of Administrative Court to Resolve Administrative Disputes in Indonesia: A Systematic Review - Saputro, Adi; Kurniawan Suriana, Ricky; Hutasoit, Erwin; Tay, Sherly; Setiawan, Budi (PT. Riset Press International, 2025)
This study examines the role of the Administrative Court (Pengadilan Tata Usaha Negara - PTUN) in resolving administrative disputes in Indonesia through a systematic literature review approach. As a crucial pillar within the Indonesian judicial system, PTUN plays a strategic function in maintaining the balance of power between the government and its citizens through independent judicial control mechanisms. This research analyzes the effectiveness of PTUN in providing legal protection for citizens' rights against arbitrary administrative actions and evaluates the implementation of general principles of good governance in administrative judicial practice. The findings indicate that PTUN has significantly contributed to upholding the principles of the rule of law and promoting accountable governance, despite facing several challenges in its implementation. These challenges encompass structural aspects including limitations in human resources and infrastructure, procedural challenges related to the complexity of procedural law, and substantial challenges regarding consistency in legal interpretation and judgment execution. Comparative analysis with international administrative court systems provides valuable insights into best practices that can be adapted within the Indonesian context. This study recommends strengthening institutional capacity through human resource development and infrastructure modernization, simplifying procedural mechanisms, harmonizing legal interpretation, and enhancing public accessibility to administrative judicial services to optimize PTUN's role in strengthening the rule of law in Indonesia.